Development of the Distinct Multiple Intelligences in Primary Students Through Interest Centers - Fredy Alonso Dueñas Macías (Asociación Colombiana de Profesores de Ingles, 2013)
This article reports on an action research study that focused on developing the distinct multiple intelligences of an English class of fifth graders through interest centers at a Colombian school. A multiple intelligences questionnaire, an open-ended observation form, and a student mini-report sheet were used to collect data. Findings revealed that through the interest centers, students maximized some of their intelligences. The implementation phase showed how careful planning, considering the students' needs and interests as well as predominant and less developed multiple intelligences, allowed the participants to follow a routine guided by activities and materials adapted to the English textbook and the school's curriculum while developing the multiple intelligences. Besides, it was found that interest centers not only foster language learning but maximize students' multiple intelligences.